Marginalization of Women: Social Stigma Against Women Recipients of the Family Hope Program Mubadalah Analysis - Ahmad Zaenudin (Brajamusti Publication, 2025)
The Family Hope Program (PKH) is a conditional social assistance program from the Indonesian government aimed at poor families to break the chain of intergenerational poverty. In practice, women are the main actors who receive and manage assistance because of their strategic position in childcare and household management. However, women who receive PKH often face social stigma that creates psychological pressure and social discrimination. This stigma is rooted in societal stereotypes that equate recipients of assistance with laziness, dependency, and failure in carrying out domestic roles. This study aims to analyze the social stigma against women who receive PKH, and to examine the extent to which the Mubadalah theory is a strategy to overcome this stigma. The study used a qualitative approach with a case study type and primary data sources in the form of in-depth interviews, participatory observations, and documentation of PKH recipients and program supporting actors in Bandar Surabaya District, Central Lampung Regency. The data were analyzed using a thematic approach and using the Mubadalah theory as the main conceptual framework that emphasizes mutuality and justice in gender relations. The results showed that most women who receive PKH experience social stigma in the form of ridicule, exclusion, and moral judgment by the surrounding community, which strengthens social and psychological marginalization. Through the application of the Mubadalah principle, this study shows that transforming mindsets and gender relations structures to be more equal can be a solution-based approach to reducing social stigma and increasing women's empowerment in managing social assistance programs more fairly and effectively